Repurposing of Acriflavine to Target Chronic Myeloid Leukemia Treatment - Nehme, Rawan; Hallal, Rawan; El Dor, Maya; Kobeissy, Firas; Gouilleux, Fabrice; Mazurier, Frédéric; Zibara, Kazem (Current Medicinal Chemistry, 2021)
Drug repurposing has lately received increasing interest in several diseases especially in cancers, due to its advantages in facilitating the development of new therapeutic strategies, by adopting a cost-friendly approach and avoiding the strict Food and Drug Administration (FDA) regulations. Acriflavine (ACF) is an FDA approved molecule that has been extensively studied since 1912 with antiseptic, trypanocidal, anti-viral, anti-bacterial and anti-cancer effects. ACF has been shown to block the growth of solid and hematopoietic tumor cells. Indeed, ACF acts as an inhibitor of various proteins, including DNA-dependent protein kinases C (DNA-PKcs), topoisomerase I and II, hypoxia-inducible factor 1α (HIF-1α), in addition to its recent discovery as an inhibitor of the signal transducer and activator of transcription (STAT). Chronic myeloid leukemia (CML) is a clonal myeloproliferative disorder characterized by the expression of the constitutively active tyrosine kinase BCR-ABL. This protein allows the activation of several signaling pathways known for their role in cell proliferation and survival, such as the JAK/STAT pathway. CML therapy, based on tyrosine kinase inhibitors (TKIs), such as imatinib (IM), is highly effective. However, 15% of patients are refractory to IM, where in some cases, 20-30% of patients become resistant. Thus, we suggest the repurposing of ACF in CML after IM failure or in combination with IM to improve the anti-tumor effects of IM. In this review, we present the different pharmacological properties of ACF along with its anti-leukemic effects in the hope of its repurposing in CML therapy.
Keywords: leukemia